Canon EOS Rebel T4i/650D for dummies - King, Julie Adair. (--For dummies., 2012)
Here's the step-by-step guide to all the features of your touchscreen dSLR! The Rebel T4i/650D has a lot of buttons, settings, and techniques to learn. This book gets you going with a complete tour of the controls, tips on getting the tough shots, and much more!--